The ballad of the sad café and other stories - McCullers, Carson, 1917-1967 (Houghton Mifflin, 2005)
This collection assembles Carson McCullers' best stories, including her study of love and longing "The Ballad of the Sad Café." A haunting tale of a human triangle that culminates in an astonishing brawl, the novella introduces readers to Miss Amelia, a formidable southern woman whose café serves as the town's gathering place. Among other works, the collection also includes "Wunderkind," McCullers' first published story, written when she was only seventeen, about a musical prodigy who suddenly realizes she will not go on to become a great pianist--From publisher description.